Die Berechnung von Machtindizes - ein Vergleich verschiedener Verfahren - N, N

Intermediaries in Buyer Seller Networks - N, N

Staatliche Regulierung in vertikal verbundenen Industrien - eine spieltheoretische Analyse - N, N

Pricing and Revenue Sharing of Bundles Using Game Theoretical Concepts - N, N

Disentangling the Relationship Between the Adoption of In-Memory Computing and Firm Performance - Fay, Maria; Müller, Oliver; vom Brocke, Jan (European Conference on Information Systems)
Recent growth in data volume, variety, and velocity led to an increased demand for high-performance data processing and analytics solutions. In-memory computing (IMC) enables organizations to boost their information processing capacity, and is widely acknowledged to be one of the leading strategic technologies in the field of enterprise systems. The majority of technology vendors now have IMC technologies in their portfolio, and the interest of companies in adopting such solutions in order to benefit from big data is increasing. Although there is first research on the business value of IMC in the form of case studies, there is a lack of large-scale quantitative evidence on the positive effect of such solutions on firm performance. Based on a unique panel data set of IMC adoption information and financial firm performance data for a sample of companies from the Fortune 500 list this study aims at explaining the relationship between the adoption of IMC solutions and firm performance. In this research-in-progress paper we discuss the theoretical background of our work, describe the proposed research design, and develop five hypotheses for later testing. Our work aims at contributing to the research streams on IT business value and business analytics by helping to better understand the nature of the interdependencies between IMC adoption and firm performance.

Identifying and quantifying cultural factors that matter to the IT workforce: An approach based on automated content analysis - Schmiedel, Theresa; Müller, Oliver; Debortoli, Stefan; vom Brocke, Jan (European Conference on Information Systems)
Organizational culture represents a key success factor in highly competitive environments, such as, the IT sector. Thus, IT companies need to understand what makes up a culture that fosters employee performance. While existing research typically uses self-report questionnaires to study the relation of culture and the success of companies, the validity of this approach is often discussed and researchers call for new ways of studying culture. Therefore, our research goal is to present an alternative ap-proach to culture analysis for examining which cultural factors matter to the IT workforce. Our study builds on 112,610 online reviews of Fortune 500 IT companies collected from Glassdoor, an online platform on which current and former employees can anonymously review companies and their man-agement. We perform an automated content analysis to identify cultural factors that employees em-phasize in their reviews. Through a regression analysis on numerical employee satisfaction ratings, we find that a culture of learning and performance orientation contributes to employee motivation, while a culture of assertiveness and gender inegalitarianism has a strong negative influence on em-ployees’ satisfaction in the IT workforce. Future research can apply our approach as an alternative method to quantifying culture and its impact on other variables.

Risk-taking incentives through excess variable compensation: Evidence from European banks - Uhde, André (The Quarterly Review of Economics and Finance)
Employing compensation data provided by 63 banks from 16 European countries for the period from 2000 to 2010 this paper empirically investigates the impact of excess variable compensation on bank risk. As a main finding, we provide evidence for a risk-increasing impact of excess variable pay for both executive variable cash-based and variable equity-based compensation. This baseline finding holds under various robustness checks, in particular when controlling for likely reverse causality between bank risk and variable compensation by employing Granger-causality tests and instrumental variable regressions. In addition, results from a large number of sensitivity analyses including board and banking characteristics as well as the financial crisis period and the quality of a country's regulatory framework provide further important implications for banking regulators and politicians in Europe.
Keywords: Banking; Executive compensation; Risk-taking; Financial stability

Are international accounting standards more credit relevant than domestic standards? - Florou, Annita; Kosi, Urska; Pope, Peter F (Accounting and Business Research)
We examine whether the credit relevance of financial statements, defined as the ability of accounting numbers to explain credit ratings, is higher after firms are required to report under International Financial Reporting Standards (IFRS). We find an improvement in credit relevance for firms in 17 countries after mandatory IFRS reporting is introduced in 2005; this increase is higher than that reported for a matched sample of US firms. The increase in credit relevance is particularly pronounced for higher risk speculative-grade issuers, where accounting information is predicted to be more important; and for IFRS adopters with large first-time reconciliations, where the impact of IFRS is expected to be greater. These tests provide reassurance that the overall enhancement in estimated credit relevance is driven by accounting changes related to IFRS adoption. Our results suggest that credit rating analysts’ views of economic fundamentals are more closely aligned with IFRS numbers, and that analysts anticipate at least some of the effects of the IFRS transition.
Keywords: IFRS; debt markets; credit ratings; credit relevance

Accounting quality in private firms during the transition to international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren (Journal of Business Economics)

Shedding light on outcome-based contracts: Benefits and risks from the buyers’ and sellers’ perspective - Böhm, Eva; Backhaus, C.; Eggert, A.; Pitsis, T. (2016 AMA Winter Academic Conference, Las Vegas, NV)

Understanding service awards: Exploit the bright side, avoid the dark side (ausgezeichnet mit Best Paper Award) - Cramer, C.; Böhm, Eva; Eggert, A. (2016 AMA Winter Academic Conference, Las Vegas, NV)

Business Service Outsourcing in Manufacturing Firms: An Event Study - Eggert, A.; Böhm, Eva; Cramer, C. (International Colloquium on Relationship Marketing (ICRM), Toulouse (nominiert für Best Paper Award))

The service award paradox - Cramer, C.; Böhm, Eva; Eggert, A. (45rd EMAC Annual Conference, Oslo)

Understanding outcome-based contracts: Benefits and risks from the buyers’ and sellers’ perspective - Böhm, Eva; Backhaus, C.; Eggert, A.; Cummins, T. (Journal of Strategic Contracting and Negotiation, (ausgezeichnet mit Best Paper Award))

Retourenmanagement zur Steigerung des Kundenwerts - Garnefeld, I.; Böhm, Eva; Feider, L. (Kundenwert: Grundlagen – Innovative Konzepte – Praktische Umsetzungen)

Service transition: A viable option for manufacturing companies with deteriorating financial performance? - Böhm, Eva; Eggert, Andreas; Thiesbrummel, Christoph (Industrial Marketing Management)
Keywords: Marketing

Auf der Suche nach dem Sinn: Corporate Social Responsibility - Schmitz, E.; Kabst, Rüdiger (PERSONALquartely)

Kommunales Bildungsmanagement - Kernkomponenten und Gelingensbedingungen - Euler, Dieter; Sloane, Peter F. E.; Fäckeler, Sina; Jenert, Tobias Johannes; Losch, Simone; Meier, Christoph; Meier, Karin; Rüschen, Eva; Schröder, Helmut
Bildung findet auf kommunaler Ebene statt. Dies ist der Ort, an dem ganz unterschiedliche Maßnahmen durchgeführt werden, die entweder nach Landesrecht, Bundesrecht oder nach den Vorschriften der Kammern reguliert sind oder aber aufgrund von privatrechtlichen Vereinbarungen zustande kommen. Kommunen sind dabei kein neutraler ‚Austragungsort’ von Bildung. Vielmehr ist das kommunale Bildungsangebot eine ganz wesentliche Größe, wenn es um die Entwicklung von Kommunen geht. Die Attraktivität und die Prosperität einer Stadt oder Gemeinde ist letztlich auch davon abhängig, welche Bildungsangebote sie den Bürgern, aber auch den Betrieben, Verbänden usw. machen kann. So gesehen hat kommunales Bildungsmanagement eine sehr zentrale Funktion zur Unterstützung und Koordination von Bildungsmaßnahmen vor Ort. Von 2009 bis 2014 hat der Bund mit dem Programm ‚Lernen vor Ort’ den Aufbau eines kommunalen Bildungsmanagements in 36 Kreisen und kreisfreien Städten gefördert. Die vorliegende Studie analysiert die dabei gewonnenen Erfahrungen, verdichtet diese zu einem Konzept des kommunalen Bildungsmanagements und zeigt auf, wie ein erfolgreiches kommunales Bildungsmanagement gewinnbringend auf andere Kommunen transferiert werden kann.

Tackling Complexity in Business and Society Research: The Methodological and Thematic Potential of Factorial Surveys - Oll, Josua; Hahn, Rüdiger; Reimsbach, Daniel; Kotzian, Peter (Business & Society)
Factorial surveys (FSs) integrate elements of survey research and classical experiments. Using a large number of respondents in a controlled setting, FSs approximate complex and realistic judgment situations through so-called vignettes—that is, carefully designed descriptions of hypothetical people, social situations, or scenarios. Despite being rooted, and predominantly applied, in sociology, FSs are particularly promising for business and society (B&S) scholars. Given the multiplicity, inherent complexity, and sometimes fuzziness of B&S research objects, conventional research methods inevitably reach their limits. This article, therefore, systematically presents methodological and thematic opportunities for FS studies in B&S research. It is argued that FSs are well suited to dealing with the complex interplay of societal-, organizational-, and individual-level factors in B&S research and to studying the principles underlying human perceptions, attitudes, values, social norms, and (anticipated) behavior. The application of the FS method is illustrated based on a showcase example in the realm of socially responsible investments (SRIs). As the literature on the conceptualization of FSs is limited, methodological challenges are addressed to guide B&S researchers past the common methodological pitfalls.
Keywords: Social Sciences (miscellaneous); Business; Management and Accounting (miscellaneous)

Human resource management and radical innovation: a fuzzy-set QCA of US multinationals in Germany, Switzerland, and the UK - Backes-Gellner, Uschi; Kluike, Marlies; Pull, Kerstin; Schneider, Martin; Teuber, Silvia (Journal of Business Economics)

Towards an importance-performance analysis of factors affecting e-business diffusion in the wood industry - Trang, S.; Zander, S.; de Visser, B.; Kolbe, L. M. (Journal of Cleaner Production)

Drivers of network governance: a multitheoretic perspective with insights from case studies in the German wood industry - Zander, S.; Trang, S.; Kolbe, L. M. (Journal of Cleaner Production)

Die Wirkungen des Outsourcings von Personalfunktionen – ein Überblick über verschiedene theoretische Ansätze und Entwicklung eines umfassenden Wirkungssets/ Effects of the outsourcing of personnel functions – an overview of several theoretical approaches and development of a comprehensive set of effects - Alewell, Dorothea; Bähring, Katrin; Thommes, Kirsten (Arbeit)
Abstract Unternehmen, die über das Outsourcing von Personalfunktionen entscheiden, stehen vor einer komplexen Fragestellung, da mit dem Bezug extern erbrachter Personaldienstleistungen sehr unterschiedliche Wirkungen ausgelöst werden können. Diverse Theorieansätze machen Aussagen zu einzelnen Wirkungskategorien des Outsourcings. Jedoch gibt bisher kein Ansatz dem Entscheidungsträger in der Praxis eine umfassende Entscheidungshilfe. Hier setzt der vorliegende Artikel an: Aus Ansätzen zur zwischenbetrieblichen Arbeitsteilung wird ein umfassendes „Wirkungsset“ des Outsourcings von Personalfunktionen hergeleitet, welches sich als Checkliste relevanter Wirkungskategorien eignet und die Einseitigkeiten bisheriger Ansätze vermeidet.
Keywords: Industrial and Manufacturing Engineering

Understanding Loyalty Program Effectiveness: Managing Target and Bystander Effects - Steinhoff, Lena; Palmatier, R. W. (Journal of the Academy of Marketing Science)

The Power of Gift Purchases in Strengthening Customer-Company Relationships - Witte, C.; Steinhoff, Lena; Eggert, A. (Proceedings of the 45th European Marketing Academy (EMAC) Conference, Oslo)

Dynamic Effects of Loyalty Rewards for Contractual Customers, Marketing Science Institute (MSI) Working Paper Series - Steinhoff, Lena; Fang, E.; Palmatier, R. W.; Wang, K.

Entwicklung, Implementierung und Evaluation eines Tagungsportfolios - Jahnke, Heike; Kehl, Verena; Kiepe, Karina (Seminar)

Insights in the OER Rating – Database – Structures, Advantages and Challenges - Beutner, Marc; Duse, Carmen; Pechuel, Rasmus; Schneider, Jennifer Nicole (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of the EU-StORe project)

Use and Implementation of OERs in Germany - Beutner, Marc; Schneider, Jennifer Nicole (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of the EU-StORe project)

Situation of visual impaired in Germany - Beutner, Marc; Schneider, Jennifer Nicole (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEL project)

The EU-StORe Project - Beutner, Marc; Schneider, Jennifer Nicole (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of the EU-StORe project)

The OER Quality Standards - Beutner, Marc; Schneider, Jennifer Nicole (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of the EU-StORe project)

Evaluation Results concerning OER and the EU-StORe Project - Beutner, Marc; Schneider, Jennifer Nicole (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of the EU-StORe project)

The Importance of OER in European Education - Beutner, Marc; Schneider, Jennifer Nicole (OER – Quality Standards, Implementation, Sharing and Use. Results and Discussions on the basis of the EU-StORe project)

The general structure of the SEEL Teacher Training Course - Beutner, Marc; Schneider, Jennifer Nicole (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEL project)

The structure of the SEEL Project - Beutner, Marc; Schneider, Jennifer Nicole (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEL project)

The Project SEEL – Basic information about the context - Beutner, Marc; Schneider, Jennifer Nicole (Sounds and Audios in E-learning scenarios. Results and Discussions on the basis of the SEEL project)

SEEL - Handbuch für Lehrkräfte - Beutner, Marc; Schneider, Jennifer Nicole

Teachers´ Manual and Teachers´ Guideline. A handbook for Teachers. - Beutner, Marc; Schneider, Jennifer Nicole

Teachers´ Manual and Teachers´ Guideline. A handbook for Teachers. - Beutner, Marc; Schneider, Jennifer Nicole

SEEL- Expertenhandbuch - Beutner, Marc; Schneider, Jennifer Nicole

SEEL- Handbook for Educators - Beutner, Marc; Schneider, Jennifer Nicole

A secured context-aware tourism recommender system using artificial bee colony and simulated annealing - Roy, Arup; Tavana, Madjid; Banerjee, Soumya; Caprio, Debora Di (International Journal of Applied Management Science)

Robust efficiency measurement with common set of weights under varying degrees of conservatism and data uncertainty - Aghayi, Nazila; Tavana, Madjid; Raayatpanah, Mohammad Ali (European J. of Industrial Engineering)

Optimistic and pessimistic performance and congestion analysis in fuzzy data envelopment analysis - Khodabakhshi, Mohamad; Tavana, Madjid; Abootaleb, Fatemeh Baghbani (International Journal of Logistics Systems and Management)

Autonomous vehicles: challenges, opportunities, and future implications for transportation policies - Bagloee, Saeed Asadi; Tavana, Madjid; Asadi, Mohsen; Oliver, Tracey (Journal of Modern Transportation)

A bi-objective inventory optimization model under inflation and discount using tuned Pareto-based algorithms: NSGA-II, NRGA, and MOPSO - Mousavi, Seyed Mohsen; Sadeghi, Javad; Niaki, Seyed Taghi Akhavan; Tavana, Madjid (Applied Soft Computing)

An Improved Method for Edge Detection and Image Segmentation Using Fuzzy Cellular Automata - Shahverdi, Reza; Tavana, Madjid; Ebrahimnejad, Ali; Zahedi, Khadijeh; Omranpour, Hesam (Cybernetics and Systems)

An integrated data envelopment analysis and free disposal hull framework for cost-efficiency measurement using rough sets - Khanjani Shiraz, Rashed; Fukuyama, Hirofumi; Tavana, Madjid; Di Caprio, Debora (Applied Soft Computing)

An optimal sequential information acquisition model subject to a heuristic assimilation constraint - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Benchmarking: An International Journal)

An integrated data envelopment analysis and simulation method for group consensus ranking - Ebrahimnejad, Ali; Tavana, Madjid; Santos-Arteaga, Francisco J. (Mathematics and Computers in Simulation)

A conceptual analytic network model for evaluating and selecting third-party reverse logistics providers - Tavana, Madjid; Zareinejad, Mohsen; Santos-Arteaga, Francisco J.; Kaviani, Mohamad Amin (The International Journal of Advanced Manufacturing Technology)

Solving Geometric Programming Problems with Normal, Linear and Zigzag Uncertainty Distributions - Khanjani Shiraz, Rashed; Tavana, Madjid; Di Caprio, Debora; Fukuyama, Hirofumi (Journal of Optimization Theory and Applications)

Multi-objective multi-layer congested facility location-allocation problem optimization with Pareto-based meta-heuristics - Hajipour, Vahid; Fattahi, Parviz; Tavana, Madjid; Di Caprio, Debora (Applied Mathematical Modelling)

Modeling synergies in multi-criteria supplier selection and order allocation: An application to commodity trading - Sodenkamp, Mariya A.; Tavana, Madjid; Di Caprio, Debora (European Journal of Operational Research)

An artificial immune algorithm for ergonomic product classification using anthropometric measurements - Tavana, Madjid; Kazemi, Mohammad Reza; Vafadarnikjoo, Amin; Mobin, Mohammadsadegh (Measurement)

A two-stage data envelopment analysis model for measuring performance in three-level supply chains - Tavana, Madjid; Kaviani, Mohamad Amin; Di Caprio, Debora; Rahpeyma, Bentolhoda (Measurement)

Managing team coordination incentives: the effect of payoff differentials - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Journal of Centrum Cathedra)

A comprehensive fuzzy DEA model for emerging market assessment and selection decisions - Khalili-Damghani, Kaveh; Tavana, Madjid; Santos-Arteaga, Francisco J. (Applied Soft Computing)

A novel artificial bee colony algorithm for shortest path problems with fuzzy arc weights - Ebrahimnejad, Ali; Tavana, Madjid; Alrezaamiri, Hamidreza (Measurement)

Loyal customer bases as innovation disincentives for duopolistic firms using strategic signaling and Bayesian analysis - Tavana, Madjid; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Annals of Operations Research)

Modeling signal-based decisions in online search environments: A non-recursive forward-looking approach - Tavana, Madjid; Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tierney, Kevin (Information & Management)

Multi-objective control chart design optimization using NSGA-III and MOPSO enhanced with DEA and TOPSIS - Tavana, Madjid; Li, Zhaojun; Mobin, Mohammadsadegh; Komaki, Mohammad; Teymourian, Ehsan (Expert Systems with Applications)

A practical taxonomy of methods and literature for managing uncertain spatial data in geographic information systems - Tavana, Madjid; Liu, Weiru; Elmore, Paul; Petry, Frederick E.; Bourgeois, Brian S. (Measurement)

A hybrid intelligent fuzzy predictive model with simulation for supplier evaluation and selection - Tavana, Madjid; Fallahpour, Alireza; Di Caprio, Debora; Santos-Arteaga, Francisco J. (Expert Systems with Applications)

An integrated intuitionistic fuzzy AHP and SWOT method for outsourcing reverse logistics - Tavana, Madjid; Zareinejad, Mohsen; Di Caprio, Debora; Kaviani, Mohamad Amin (Applied Soft Computing)

An extended VIKOR method using stochastic data and subjective judgments - Tavana, Madjid; Kiani Mavi, Reza; Santos-Arteaga, Francisco J.; Rasti Doust, Elahe (Computers & Industrial Engineering)

Modeling Sequential Information Acquisition Behavior in Rational Decision Making - Tavana, Madjid; Di Caprio, Debora; Santos Arteaga, Francisco J. (Decision Sciences)

Die Sanktionierung von Verstößen gegen die Erläuterungs- und Bonitätsprüfungspflicht im Verbraucherkreditrecht - Bartlitz, David (Wertpapier-Mitteilungen (WM))

Die Haftung des Kommanditisten auf der Grundlage kapitalgesellschaftsrechtlicher Prinzipien - Bartlitz, David

Keine Verwirklichung des Rechts zum Widerruf trotz Erklärung erst zwei Monate nach Darlehensrückführung und Zahlung einer Vorfälligkeitsentschädigung. Anmerkung zu OLG Frankfurt a.M., Urt. v. 27.01.2016 - 17 U 16/15 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Supporting Business Model Idea Generation Through Machine-generated Ideas - Towards a Design Theory - John, Thomas (AIS SIGPRAG Pre-ICIS Workshop: Practice-based Design and Innovation of Digital Artifacts)

Strategic Formation of Customer Relationship Networks - Brangewitz, Sonja; Haake, Claus-Jochen; Möhlmeier, Philipp
We analyze the stability of networks when two intermediaries strategically form costly links to customers. We interpret these links as customer relationships that enable trade to sell a product. Equilibrium prices and equilibrium quantities on the output as well as on the input market are determined endogenously for a given network of customer relationships. We investigate in how far the substitutability of the intermediaries' products and the costs of link formation influence the intermediaries' equilibrium profits and thus have an impact on the incentives to strategically form relationships to customers. For networks with three customers we characterize locally stable networks, in particular existence is guaranteed for any degree of substitutability. Moreover for the special cases of perfect complements, independent products and perfect substitutes, local stability coincides with the stronger concept of Nash stability. Additionally, for networks with n customers we analyze stability regions for selected networks and determine their limits when n goes to infinity. It turns out that the shape of the stability regions for those networks does not significantly change compared to a setting with a small number of customers.

A Metric for Candidate Selection for a Robust Opportunistic Container Routing in high Complex Distribution Centers - Kopecki, Lukas

A Technical Approach of a Simulation-Based Optimization Platform for Setup-Preparation via Virtual Tooling by Testing the Optimization of Zero Point Positions in CNC-Applications - Weber, Jens (Proceedings of the 2015 Winter Simulation Conference)

A Comparison of the Usage of Different Approaches for the Management of Plant Engineering Projects - Akbulut, Akin; Laroque, Christoph; Wenzel, Sigrid; Jessen, Ulrich (Proceedings of the 2015 Winter Simulation Conference)
Customized planning, engineering and construction of one-of-a-kind products (like wind energy, biogas or power plants) are complex and contain a lot of risks and temporal uncertainties, e.g. of logistics and project schedules. Therefore the management of this kind of projects has to be supported by adequate methods for the estimation of project risks and uncertainties. Based on the results of the joint research project simject of the Universities of Paderborn and Kassel, which aims at the development of a demonstrator for simulation-based and logistic-integrated project planning and scheduling, this paper discusses the usage of different approaches for supporting project management of plant engineering projects. After a short introduction and description of the approaches to be compared a wind energy plant as evaluation model as well as the application of the different methods are presented. Additionally, the usage of the approaches is compared and the advantages and disadvantages are pointed out.

A Deadlock-Free Route Reservation Method for Automatized Decentralized Controlled Transportation in High Complex Distribution Centers - Kopecki, Lukas

Sharing Means Caring? Hosts' Price Reactions to Rating Visibility - Gutt, Dominik; Herrmann, Philipp (Proceedings of the 23rd European Conference on Information Systems (ECIS), Münster)
We empirically investigate how hosts on Airbnb, a popular peer-to-peer website for fee-based sharing of under-utilized space, adjust their prices once their offering gets a visible star rating for the first time. We use data for over 14,000 offerings from Airbnb which we collected for New York City. Our findings indicate that hosts whose offerings achieve star rating visibility significantly increase their prices by an average of 2.69 € more than hosts with comparable offerings who do not experience this rating visibility during the time of observation. Out of all offerings who achieve rating visibility, we identify the upper quartile of hosts to be the main driver of this price increase, whereas the first 75% percent show only a marginal price reaction. These results can serve as a first step towards understanding the motivation of people to provide assets to the sharing economy.

A Robust Opportunistic Routing for High complex Decentralized controlled Distribution Center - Kopecki, Lukas

Implementation and Comparison of Cluster-Based PSO Extensions in Hybrid Settings with Efficient Approximation - Mueß, André; Weber, Jens; Reisch, Raphael-Elias; Jurke, Benjamin (Proceedings of the First Conference of Machine Learning for Cyber Physical Systems)

Protocol Structure for Controlling Adaptive Conveyor System in Automatized High Complex Distribution Centers - Kopecki, Lukas

A System for Uncovering Latent Connectivity of Health Care Providers in Online Reviews - Baeumer, Frederik Simon; Geierhos, Michaela; Schulze, Sabine (Information and Software Technologies: 21th International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015, Proceedings)

Find a Physician by Matching Medical Needs described in your Own Words - Baeumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela

An approach for deadlock Prevention in decentralized controlled pre-storage zones with dynamic behavior and time windows - Kopecki, Lukas (International Journal of Materials, Mechanics and Manufacturing)

Der zufriedene Patient 2.0: Analyse anonymer Arztbewertungen im Web 2.0. - Geierhos, Michaela; Schulze, Sabine; Baeumer, Frederik Simon (Working Papers des KVF NRW)

Online-Optimierung zur Festlegung von Bestellzeitpunkten in der Losgrößenfertigung - Dangelmaier, Wilhelm (Schenk, Michael;Zadek, Hartmut;Müller, Gerhard;Richter, Klaus;Seidel, Holger (Hrsg.): 20. Magdeburger Logistiktage "Sichere und nachhaltige Logistik")

Filtering Reviews by Random Individual Error - Geierhos, Michaela; Baeumer, Frederik Simon; Sabine, Schulze; Valentina, Stuß (Current Approaches in Applied Artificial Intelligence, Lecture Notes in Computer Science)

I grade what I get but write what I think." Inconsistency Analysis in Patients‘ Reviews - Geierhos, Michaela; Baeumer, Frederik Simon; Schulze, Sabine; Stuß, Valentina (ECIS 2015 Completed Research Papers)

Hardware in the Loop Framework for decentralized autonomous conveyor in automatic pre-storage zones - Kopecki, Lukas

Asynchronous Optimization Techniques for Distributed Computing Applications - Reisch, Raphael-Elias; Weber, Jens; Laroque, Christoph; Schröder, Christian (Proceedings of the 2015 Spring Simulation Multi-Conference)

Analyzing Supply Chain Nodes in Heterogeneous Environments Based on Transaction Data with Respect to Independent Item Behavior - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (International Journal of Advances in Computer Science & Its Applications - IJCSIA)

Online optimization to determine order times - Dangelmaier, Wilhelm, Wilhelm

Identifikation kognitiver Effekte in Online-Bewertungen - Geierhos, Michaela; Stuß, Valentina

Second-hand experience reports: Findings {\ "about the authorship of doctor reviews in online portals - Geierhos, Michaela; Baeumer, Frederik Simon

What did you mean? Facing the Challenges of User-generated Software Requirements - Geierhos, Michaela; Schulze, Sabine; Baeumer, Frederik Simon (Proceedings of the 7th International Conference on Agents and Artificial Intelligence)

Analytical derivation of the sequence rules for the equalization of high-volume job features - Markwart, Paul

Prescriptive Analytics for Planning Research-Performance Strategy - Minhee, Cho; Weber, Jens; Song, Sa-kwang; Jung, Hanmin; Lee, Mikyoung (Computer Science and Its Applications - Ubiquitous Information Technologies)

Interpersonal relations in biographical dictionaries. A case study - Stotz, Sophia Charlotte; Stuß, Valentina; Reinert, Matthias; Schrott, Maximilian (Proceedings of the First Conference on Biographical Data in a Digital World)

The satisfied patient 2.0: Analysis of anonymous doctor reviews to generate a patient mood - Geierhos, Michaela; Schulze, Sabine (ForschungsForum Paderborn)